IDENTIFIKASI SARANA DAN PRASARANA PENDIDIKAN JASMANI SD DI KEMANTREN MERGANGSAN KOTA YOGYAKARTA - Pratama, Teddy Giolanda (Jurnal Pendidikan Dasar dan Aktifitas Jasmani, 2025)
This research aims to determine the presence, condition, and ownership status of physical education facilities in primary schools (SD) in the Mergangsan Subdistrict of Yogyakarta City. This research is a quantitative descriptive study. The method used in this research is a survey method with research instruments in the form of observation sheets. The total population of this research is 10 primary schools in the Mergangsan Subdistrict. Data from this research were analyzed using descriptive analysis techniques, which were then interpreted into percentages. The results of this research revealed that the condition of physical education equipment in primary schools in the Mergangsan Subdistrict is generally good, with a percentage of 98.8% indicating good condition, and only 1.2% indicating damaged equipment. Meanwhile, the condition of physical education facilities in primary schools in the Mergangsan Subdistrict is also favorable, with a percentage of 94.62% indicating good condition, and 5.38% indicating damaged facilities. As for the condition of physical education facilities in primary schools in the Mergangsan Subdistrict, 92% are in good condition, while 8% are in a damaged state.